Antioxidant effect of omega-3 fatty acids on exercise-induced oxidative stress in rats - Sarikaya, M.; Aslan, M.; Cinar, V.; Cibuk, S.; Selcuk, M.; Embiyaoglu, N. M.; Oge, B. (Verduci Publisher, 2023)
OBJECTIVE: The aim of this study is to examine the effects of omega-3 supplementation on Catalase (CAT) activity, Malondialdehyde (MDA), advanced oxidation protein products (AOPP) and reduced glutathione (GSH) levels in long-term aerobic exercises in rats. MATERIALS AND METHODS: 28 male Wistar albino rats (8 weeks old, 220-350 g body weight) were included in the study. The rats were given treadmill exercise for 20 minutes at an average speed of 15 cm/s, 5 days a week, for 8 weeks. The experiment was terminated at the end of the eighth week. Blood samples were taken. CAT, MDA, AOPP and GSH analyses were performed. SPSS v. 21 package program was used in the analysis of the data. The distribution of the data was examined with the normality homogeneity test, and it was determined that it was a normal distribution. As a result, the One-Way ANOVA test, one of the parametric tests, was used. Tukey test was used to determine the difference between groups. Significance levels were evaluated as (p < 0.05). RESULTS: Statistical analysis showed a statistically significant difference between groups in CAT, MDA and GSH levels (p < 0.05), while there were no differences between the groups in AOPP levels ( p > 0.05). CONCLUSIONS: In the conclusion of the study, it was determined that omega-3 supplementation caused a decrease in MDA level, an increase in CAT activity and GSH level in rats exposed to chronic long-term exercise. Thus, it can be said that omega-3 supplementation in chronic long-term exercise will provide antioxidant protection against potential oxidative damage.
Keywords: Antioxidant; Chronic exercise; Omega-3; Free radicals